2020
DOI: 10.4236/jbpc.2020.113003
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-Methylated Oligonucleotides Past, Present and Future

Abstract: At the moment, we see a great interest for application of Anti Sense Oligonucleotides (ASOs) in order to regulate the expression of genes related to certain diseases. These nucleotides obtained a number of fascinating properties by means of chemical manipulation of natural DNA and RNA under conservation of Watson-Crick base-pairing. About 35 years ago for our research in this field, we selected synthetically (short) phosphate-methylated DNA and RNA. It was concluded that there is an exclusive selection in hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Recently, it was observed that DNA binding force facilitates Z-DNA formation under physiological salt conditions [2]. Generally, the impact of the presence of methyl phosphotriester (MPTE) linkages of the DNA backbone results in higher nuclease stability and the benefit of lipophilic character as has been demonstrated under biological conditions [3]. The MPTE linkages also improve the duplex stability due to the reduction of the electrostatic repulsion between the strands by eliminating the negative charge in one strand [4].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Recently, it was observed that DNA binding force facilitates Z-DNA formation under physiological salt conditions [2]. Generally, the impact of the presence of methyl phosphotriester (MPTE) linkages of the DNA backbone results in higher nuclease stability and the benefit of lipophilic character as has been demonstrated under biological conditions [3]. The MPTE linkages also improve the duplex stability due to the reduction of the electrostatic repulsion between the strands by eliminating the negative charge in one strand [4].…”
Section: Introductionmentioning
confidence: 95%
“…After base protection, the phosphodiester backbone was methylated as described by Miller et al [18] followed by base deprotection. In the context of a recombinant DNA study, we used the E. coli pab B gene, coding for para aminobenzoate synthetase, inserted in the M13mp18 phage selecting 2 templates for relative synthesis activity of complementary phosphatemethylated 8-and 18-mers along the template position [3].…”
Section: Synthesis Of Mpte Dnasmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ), was investigated and applied to the DNA sequencing based on field effect transistor (Chen et al 2013). The advantages of MPTE modifications on the DNA backbone result in higher nuclease stability and the emergence of lipophilic character (Buck 2020). Moreover, MPTE modifications improve duplex hybridization affinity due to the reduction of electrostatic repulsion (reduction of a negative charge for each MPTE linkage) between the strands of an nDNA/DNA,RNA duplex (Chou et al 2022; Huang et al 2018; Kuo et al 2020; Meade et al 2014; Miller et al 1986; Moody et al 1989).…”
Section: Introductionmentioning
confidence: 99%